Willingness to administer mouth-to-mouth ventilation in a first response program in rural Bangladesh. Issue 1 (December 2015) - Mecrow, Tom; Rahman, Aminur; Mashreky, Saidur; Rahman, Fazlur; Nusrat, Nahida; Scarr, Justin; Linnan, Michael
Abstract Background Timely mouth-to-mouth ventilation is critical to resuscitate drowning victims. While drowning is frequent, there are no lay persons trained in cardio-pulmonary resuscitation (CPR) in rural Bangladesh. As part of a feasibility study to create a first response system in a conservative Islamic village environment, a pilot was undertaken to examine willingness to provide mouth-to-mouth ventilation for drowning resuscitation. Methods A questionnaire was administered to 721 participants at the beginning of a village-based CPR training course. Trainees were asked regarding willingness to administer mouth-to-mouth ventilation on a variety of hypothetical victims. Responses were tabulated according to the age, sex and relationship of the trainee to the postulated victim. Results Willingness to deliver mouth-to-mouth ventilation was influenced by sex of a potential recipient and relationship to the trainee. Adolescent participants were significantly more willing to perform mouth-to-mouth ventilation on someone of the same sex. Willingness increased for both sexes when the postulated victim was an immediate family member. Willingness was lower with extended family members and lowest with strangers. Adult trainees were more likely to perform mouth-to-mouth ventilation than adolescent trainees in any scenario. Conclusion Adults express more willingness to resuscitate a broader range of drowning victims than adolescents. However in rural Bangladesh, adolescents are more likely to be in close proximity to a drowning in progress. Further efforts are needed to increase willingness of adolescents to provide resuscitation to drowning victims. However, despite potential cultural limitations, trained responders appear to be willing to give mouth-to-mouth ventilation to various recipients. Final determination will require evidence on response outcomes which is being collected.